THE KABOWEI-IJAW AND GREAT BRITAIN IN THE ‘AGE OF EMPIRE’: A STUDY IN RESISTANCE AGAINST IMPERIAL DOMINATION IN SOUTHERN NIGERIA - Ekpotuatin Charles Ariye; Uwomano Benjamin Okpevra (Romanian Journal of Historical Studies, 2024)
This paper is an addition to scholarship on resistance to colonialism in Southern Nigeria. The paper underscores some important but neglected facts that triggered questions about the state of scholarship on indigenous peoples’ resistance against Great Britain’s imperial and colonial expansion in the region. It is evident that, most often, existing scholarship on resistance to imperialism tends to focus on the so-called big ‘ethnic groups’ with centralized political systems. Little or nothing has been done about the experiences of smaller groups in their encounters with the imperial powers. Thus, this study revealed some unknown facts, especially about the Kabowei people of the Western Niger Delta in their relations with Great Britain. It became evident that what we know as the standard historiography of the general relations between the various peoples of the Western Delta and Great Britain is not fully captured in the existing historiography. There are lots of gaps, which require filling in. It is, therefore, on the heels of such inherent gaps that this study examined and brought to light the experiences of the Kabowei-Ijaw about Great Britain’s imperial expansions within the period under review. From the findings, the Nigerian story of resistance to alien domination cannot be considered complete without including the Kabowei experience.